2004
DOI: 10.1002/chin.200406259
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Reversal Agents

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 1 publication
1
53
1
2
Order By: Relevance
“…Third-generation modulators that specifically and potently inhibit P-glycoprotein have been developed to overcome the limitations of the previous ones (8,14). Although the preliminary results of ongoing clinical trials are hopeful, their efficacy in cancer patients has not yet been shown (15). Therefore, in anticipation of a possible clinical failure of the third-generation modulators currently under study or to complement them in case of success, it is still necessary to search for new, efficient P-glycoprotein modulators without undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Third-generation modulators that specifically and potently inhibit P-glycoprotein have been developed to overcome the limitations of the previous ones (8,14). Although the preliminary results of ongoing clinical trials are hopeful, their efficacy in cancer patients has not yet been shown (15). Therefore, in anticipation of a possible clinical failure of the third-generation modulators currently under study or to complement them in case of success, it is still necessary to search for new, efficient P-glycoprotein modulators without undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Since MDR mediated by Pgp has been documented in a variety of human cancer cells and in same case, such as in some carcinomas including breast, ovarian, and renal, has been shown to be associated with a poor response to cancer chemotherapy, [7][8][9][10][11][12][13][14][15][16] UFH could be used as chemosensitizer in the clinical setting to inhibit the mechanism of pleiotropic chemoresistance Pgp-mediated and to potentiate chemotherapy. 17,18 In this study, we evaluated the in vitro effects of UFH on the Pgp function and activity using a human breast cancer cell line, such as MDA-MB-231 19 and assessed whether these effects increased the sensitivity of this carcinoma cell type to antineoplastic drugs. The functional ability of Pgp was tested by measuring intracellular retention of the MDR Pgp-mediated marker, calcein acetoxymethylester (calcein-AM).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] An obstacle in applying classical MDR modulators arises from their commonly occurring intrinsic toxicity at doses necessary to be active, for example, heart failure, hypotension, hyperbilirubinemia, and immunosuppression by cyclosporin A. Moreover, improved so-called second-generation MDR modulators were demonstrated to induce enhanced activity of liver enzymes of the family of cytochrome P450 mixed-function oxidases resulting in an increased pharmacokinetic turn over of the applied anticancer drugs.…”
mentioning
confidence: 99%